Medical Tourism in the Context of National Health Systems` Institutional Characteristics - OSADCHUK, M. A.; OSADCHUK, A. M.; TRUSHIN, M. V. (Journal of Environmental Management and Tourism; Vol 11 No 2 (2020): JEMT Volume Xi Issue 2(42) Spring 2020, 2020)
Medical tourism (MT) is a modern type of medical services outside the state of residence. It links medicine and tourism. Moreover, its availability combined with economic feasibility is the main incentive for seeking medical care outside the place of residence and is an important issue for national health systems. A noticeable MT contribution to the country`s economy is possible if there is a well-thought-out infrastructure with introduction of certification procedure, a universal service and marketing system, an adequate response to the offer of additional tourism services and regulation of conditions for systematic cooperation with private intermediaries. However, the absence of interstate standards for this type of medical care leads to significant ethical, political, epidemiological and economic problems and makes it difficult to assess its professional quality. This necessitates the creation of a legal framework that takes into account the rights and responsibilities of both the medical services consumer and the host country.